Development of the Magic Cube Numbers Educational Tool to Enhance Symbolic Thinking Skills in Children Aged 4-5 Years - Khodarsih, Delma; Sari, Meliana; Pérez, Carlos (CV Berkah Syahdin Trust, 2025)
Purpose – Symbolic thinking is a fundamental cognitive ability that enables children to understand and use symbols, such as numbers and letters, to represent real-world concepts. This study aims to develop the Magic Cube Numbers educational tool to enhance symbolic thinking skills in children aged 4–5 years. Design/methods/approach – This research utilizes a Research and Development (R&D) approach, adopting the 4D model by Thiagarajan—Define, Design, Develop, and Disseminate—while focusing on the Develop stage. Data were collected using expert validation sheets and teacher practicality questionnaires, with evaluations conducted by two expert validators and two practitioner teachers. Findings – The Magic Cube Numbers tool obtained a validity score of 82.14%, categorized as